New drought indices - Niemeyer S. (Drought management: scientific and technological innovations, 2008)
In this paper drought indices from different disciplines and derived from different data sources are reviewed. For each category of meteorological, hydrological, agricultural, comprehensive, remote sensing-based, and combined drought indices the current state of development is described. While in the field of remote sensing derived drought indices every year a large number of new indices is proposed, in function of new datasets that become available, the development of new drought indices based on meteorological and hydrological data is more focused on practical applications. The combination of drought indices from different domains seems to be the most promising, but also the most demanding way forward to draw a comprehensive picture of a drought situation.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)